Synthesis, Characterization and Antibacterial Properties of Nickel(II) Complex with 4-Aminoantipyrine Ligand - Yusica Amalia Rasyda; Mudhita Kusuma Widowati; Soerya Dewi Marliyana; Sentot Budi Rahardjo (Universitas Gadjah Mada, 2021)
The novel nickel(II) complex has been successfully synthesized through the reaction of Ni(NO3)2·6H2O with 4-aminoantipyrine (AAP) ligand in a 1:3 mole ratio of Ni(II) to AAP. The complex was characterized using UV-Vis, Atomic Absorption Spectroscopy (AAS), Infrared spectrophotometry (IR), Thermogravimetry/Differential Scanning Calorimetry (TG/DSC), conductivity, and magnetic susceptibility. The complex formula was [Ni(AAP)3](NO3)2·5H2O. AAP was a bidentate ligand that coordinated through the primary amine nitrogen and the carbonyl oxygen to the nickel ion. The electronic spectra of the complex displayed two peaks at 646 nm and 385 nm in accordance with the 3A2g(F) → 3T1g(F) and 3A2g(F) → 3T1g(P) transitions, respectively. This complex gave a paramagnetic property with the effective magnetic moment (µeff) of 2.96 BM and the shape of an octahedron. The antibacterial test of this complex showed higher activity than the metal and its free ligand.